Exposing First-Semester Accounting Students to Accounting Periodicals. - Raff, Michael C. (The Accounting Review, 1971)
Abstract The article focuses on exposing first-semester accounting students to accounting periodicals. Since many introductory accounting courses include a substantial amount of bookkeeping-type work, students often develop a conception of accounting as a dry and unstimulating field. This viewpoint can often be radically altered by exposing first-semester accounting students to the activities of professional accountants. In order to expose the first-semester introductory accounting students to the activities of accountants and to give them a much broader perspective of accounting than can be derived from their textbooks, each of the students are required to select an article from one of several accounting periodicals and prepare a written report on the article. Students are encouraged to select articles that are both interesting and understandable to them. They are asked to avoid overly technical articles such as those dealing with complex tax matters. Most students are able to find suitable articles in recent issues of The Journal of Accountancy. Other recommended sources of accounting articles are The Accounting Review, Management Accounting and The Federal Accountant.